Garnier Cosmetic Product Purchase Decision Analysis - Muhamad Fizky Yusuf; Prasetyo Hadi; Alfatih S. Manggabarani (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2022)
Developments in the business world cannot be denied, one of which is the development in the cosmetic sector, this is marked by the emergence of many brands and types of cosmetic products that make consumers have to think about making purchasing decisions. Garnier is one of the cosmetic brands in Indonesia, especially Jakarta. The purpose of this study was to determine whether purchasing decisions for Garnier cosmetic products were influenced by trust, country of origin and product quality. This research is a quantitative research using Partial Least Square (PLS) software. The sample in this study were 120 respondents spread across the Jakarta area. The results of this study indicate that country of origin has no effect on purchasing decisions, product quality affects purchasing decisions, country of origin affects purchasing decisions through trust, product quality affects purchasing decisions through trust and trust affects purchasing decisions. Keywords : country of origin, product quality, trust, purchasing decisions